1999
DOI: 10.1046/j.1529-8817.1999.3520339.x
|View full text |Cite
|
Sign up to set email alerts
|

GENETIC, MORPHOLOGICAL, AND TOXICOLOGICAL VARIATION AMONG GLOBALLY DISTRIBUTED STRAINS OF NODULARIA (CYANOBACTERIA)

Abstract: Morphological, toxicological, and genetic variation was examined among 19 strains of Nodularia. The strains examined could be morphologically discriminated into four groups corresponding to N. spumigena Mertens, N. sphaerocarpa Bornet et Flahault, and two strains that did not clearly correspond to currently accepted Nodularia species. Genetic variation was examined using nucleotide sequencing of the phycocyanin intergenic spacer region (cpcBA‐IGS) and RAPD‐PCR. The PCR‐RFLP of the cpcBA‐IGS differentiated four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(83 citation statements)
references
References 39 publications
5
76
2
Order By: Relevance
“…The delineation of N. spumigena type strains PCC 73104 and PCC 73104/1 here as N. sphaerocarpa is in agreement with their morphological and genetic classification into the N. sphaerocarpa cluster in other studies (Bolch et al, 1999;Lehtimäki et al, 2000;Laamanen et al, 2001;. According to our results, and the fact that N. spumigena was already described in 1886 according to the botanical system, a new bacteriological type strain ought to be assigned to N. spumigena.…”
Section: Designations Of Benthic Nodularia Strainssupporting
confidence: 91%
See 2 more Smart Citations
“…The delineation of N. spumigena type strains PCC 73104 and PCC 73104/1 here as N. sphaerocarpa is in agreement with their morphological and genetic classification into the N. sphaerocarpa cluster in other studies (Bolch et al, 1999;Lehtimäki et al, 2000;Laamanen et al, 2001;. According to our results, and the fact that N. spumigena was already described in 1886 according to the botanical system, a new bacteriological type strain ought to be assigned to N. spumigena.…”
Section: Designations Of Benthic Nodularia Strainssupporting
confidence: 91%
“…These studies revealed variation among Baltic N. spumigena strains sharing identical 16S rRNA genes. In addition, fingerprinting methods such as RAPD-PCR on Baltic Sea and Australian strains (Bolch et al, 1999), and repetitive extragenic palindromic sequence-and enterobacterial repetitive intergenic consensus-PCR on the Baltic Sea strains (Lehtimäki et al, 2000) yielded a more diverse picture of the N. spumigena cluster than that shown by STRR in this study. The benthic N. sphaerocarpa and N. harveyana were more diverse than the planktonic N. spumigena, as shown by all methods used.…”
Section: Phylogenetic Relationships Within the Genus Nodulariamentioning
confidence: 48%
See 1 more Smart Citation
“…Aquat Microb Ecol 32: [251][252][253][254][255][256][257][258][259] 2003 brackish environments of the world (Sellner 1997, Bolch et al 1999, Moisander & Pearl 2000, arousing public concern over their potential toxicity. In recent years, long-term data showed increasing trends in bloom quantity and intensity in the Baltic Basin (Finni et al 2001).…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…Baltic Nodularia strains have been shown to produce nodularin, a hepatotoxic cyclic pentapeptide which can act as a liver tumor promoter and direct carcinogen (Carmichael et al 1988, Sivonen et al 1989. Extensive blooms of Nodularia are globally distributed in the Morphometric variability of the genus Nodularia (Cyanobacteria) in Baltic natural communities brackish environments of the world (Sellner 1997, Bolch et al 1999, Moisander & Pearl 2000, arousing public concern over their potential toxicity. In recent years, long-term data showed increasing trends in bloom quantity and intensity in the Baltic Basin (Finni et al 2001).…”
Section: Introductionmentioning
confidence: 99%